COMMUNISM AND DE-COMMUNIZATION: STUDY OF THE RISE AND COLLAPSE OF COMMUNISM IN INDONESIA AND UKRAINE: A COMPARISON - Rambe, Safrizal; Chrisnandi, Yuddy; Haran, Olexiy (Department of Government, FISIP, Universitas Padjadjaran, 2024)
The rise and fall of communism have caught the attention of many observers, including Indonesia and Ukraine. It is interesting to observe that communism in both countries had received comprehensive support during its revival but ended in destruction in Indonesia and Ukraine, which used to be countries that had the ideology of communism and later denounced communist regimes and banned propaganda of its symbols. This study wants to compare the existence of communism in Indonesia and Ukraine by referring to aspects of ideology and people's acceptance, forms and ideologies adopted by the two countries, figures who propagated it, supporting organizations, and the collapse of communism in Indonesia and Ukraine. This study uses a qualitative method by prioritizing library research in data collection, which then analyses and explains the meaning of the data or interprets it as accurately as possible.gb777